The legend of Zorro - Campbell, Martin; Orci, Roberto; Kurtzman, Alex; Banderas, Antonio; Zeta-Jones, Catherine, 1969-; Sewell, Rufus, 1967-; Chinlund, Nick, 1961-; McCulley, Johnston, 1883-1958; Columbia Pictures; Spyglass Entertainment (Firm); Amblin Entertainment (Firm) (Culver City, CA : Sony Pictures Home Entertainment, 2006)
This time, the legendary Zorro fights against evil-doers with the help of his beautiful wife, Elena, and their precocious young son, Joaquin. Alejandro De LaVega is torn between two worlds: his life as Zorro and his life as a family man. After Alejandro once again breaks his promise to stop wearing the mask, Elena leaves him, and she soon begins seeing Armand, a haughty French Count. But a mysterious explosion in the desert leads Zorro to believe that there's more to Armand than meets the eye. Zorro becomes intent on finding out what that is. Little does he know, there are others working to uncover certain truths as well.
Based on the character created by Johnston McCulley.
Director of photography, Phil Meheux ; editor, Stuart Baird ; music, James Horner ; costume designer, Graciela Mazón ; production designer, Cecilia Montiel ; visual effects supervisor, Kent Houston.
Antonio Banderas, Catherine Zeta-Jones, Rufus Sewell, Nick Chinlund.
MPAA rating: PG; for sequences of violence/peril and action, language and a couple of suggestive moments.
DVD, region 1, widescreen presentation; Dolby Digital.
In English or French; subtitles in English or French; closed-captioned.
Keywords: Zorro -- (Fictitious character) -- Drama; Married people -- Drama; Undercover operations -- Drama; French language materials; Western films; Action and adventure films; Feature films; Video recordings for the hearing impaired